The Difference in Loneliness Scores Before and After Being Given Gestalt Empty Chair Therapy Among Divorce Victim Students - Silfa, Sulasi Arosidu; Estria, Suci Ratna; Etlidawati, Etlidawati; Prasetya, Rikhan Luhur (Sarana Ilmu Indonesia (Salnesia), 2025)
Divorce is a social phenomenon that has various impacts on cultural, economic, and psychological conditions around the world. Divorce not only has an impact on the husband and wife, but also has an impact on other families, especially on children. Divorce can increase the risk of mental health problems in children , one of which is loneliness. This study aimed to determine the the effect of Gestalt empty chair Therapy on loneliness scores experienced by UMP S1 Nursing students. This quantitative research used a pre-experimental design with one group pretest-posttest involving 50 subjects selected through purposive sampling. The level of loneliness was measured using the UCLA Loneliness Scale Version 3, and data were analyzed using IBM SPSS Statistics 27. Univariate analysis was used to describe the characteristics of subjekts, while bivariate analysis was conducted using the Paired Sample t-test to determine the difference of the intervention. The results showed that the average loneliness score before the intervention was 53,68 and decreased to 45,10 after the intervention. The paired sample t-test indicated a significant difference of Gestalt empty chair Therapy on reducing loneliness with a p-value of 0,001 (p-value < 0,05). In this study, gestalt empty chair therapy was effective in overcoming the feeling of loneliness of students who are victims of divorce. Through this technique, students were able to express pent-up emotions and resolve internal conflicts, thereby improving their emotional well-being.